Effect of breed and Diacylglycerol acyltransferase 1 gene polymorphism on milk production traits in Beninese White Fulani and Borgou cows - Houaga, I.; Muigai, Anne W.T.; Kyallo, Martina M.; Githae, D.; Youssao, I.A.K.; Stomeo, Francesca (2017)
Diacylglycerol acyltransferase 1 (DGAT1) is a potential candidate gene with a non-conservative substitution of lysine by alanine (K232A) in exon 8 having a major effect on milk production traits in cattle. The aim of this study was to analyze the allele and genotype frequency, and investigate the association of the DGAT1 K232A polymorphism with milk production traits in indigenous White Fulani and Borgou cattle breeds in Benin. In total, 103 White Fulani and 103 Borgou were genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphisms and validated by Sanger sequencing. The genotypic frequencies of KK, KA and AA in White Fulani and Borgou breeds were 0.83, 0.16, 0.01 and 0.57, 0.39, 0.04 respectively. Frequencies of K and A alleles were 0.91 and 0.09, and 0.77 and 0.23 in White Fulani and Borgou breeds respectively. The White Fulani cows showed higher daily milk yield (P< 0.01), lactose content (P<0.001), protein yield (P< 0.01) and fat yield (P<0.01) compared to Borgou. The DGAT1 KK genotype was significantly (P<0.05) associated with higher fat yield in White Fulani. Therefore, the DGAT1 locus could serve as a genetic marker for selection of fat yield in indigenous White Fulani Cows. Further studies would be needed to investigate the effect of DGAT1 gene on milk fatty acids variation between the two breeds.